Theoretical justification of influence of electric field on lubricating media - Трофімов, Ігор Леонідович (Eastern-European Journal of Enterprise Technologies, 2013)
The article concerns the application of the electric field to ensure the stabilization of operational properties of the lubricating media and presents the results of our research in this area. The main purpose of this research is the theoretical justification of influence of the electric field on the tribological properties of the lubricating media and formation of the mathematical dependences, which describe the influence. The high specifications for the lubricating media define the need to improve the tribological properties of the existing lubricating media, and to find new methods and technologies for production of the lubricating media for machinery. The article justifies the ideas concerning the mechanism of interaction of molecules of the lubricating media and their parts under the influence of external electric and natural electrostatic fields, on the basis of the analyzed works and results of our research. The presented theoretical justification of the influence of the electric field on the working fluids permitted to obtain the mathematical dependences, to analyze and model the influence of the electric field on the tribological properties of the lubricating media, and to obtain the explanation of the relation between the main physical parameters of tribosystems and the electric field. The results of this work can be used to improve the performance properties of the working fluids, in particular anti-wear properties by means of the electric field. The research results can be applied by tribologists, chimmotologists, as well as by specialists in the sphere of operation of fuel and lubricating systems of ground and aviation equipment.